Role of Local Tranexamic Acid for The Prevention of Surgical Bleeding in Soft-Tissue Surgery - Sarhandi, Zainab; Ghayasuddin, Muhammad; Nastaeen Sarhandi, Marium; Zia, Wahb Noor (Biological and Clinical Sciences Research Journal, 2025)
Surgical bleeding is a common concern in soft-tissue procedures, often necessitating interventions to minimise blood loss and associated complications. Tranexamic acid (TXA), an antifibrinolytic agent, has been widely used to reduce surgical bleeding. However, the comparative effectiveness of local versus systemic TXA administration remains an area of ongoing investigation. Objective: The present study aims to evaluate the role of local tranexamic acid in preventing surgical bleeding in soft-tissue surgery. Methods: After the ethical approval from the institutional review board, this retrospective observational study was conducted at Kulsum Bai Valika Hospital, Karachi, from 1st April 2023 to 30th April 2024. Through non-probability sampling, a sample of 100 patients, aged 20-80 years, either gender, who underwent different soft tissue surgeries that included general surgery, orthopaedics, and gynaecology, were included in the present study. TXA treatment was grouped according to the type of surgery involved and the method used to apply the TXA. The three groups were local TXA, systemic TXA, and no-TXA groups. Local TXA meant that TXA was applied directly to the surgery site, while systemic TXA was given through a drip. Results: The mean blood loss was 499.16 mL in the Local TXA group, 557.84 mL in the Systemic TXA group, and 552.45 mL in the No TXA group (p= 0.668). However, the incidence of postoperative bleeding was significantly lower in the Local TXA group (26%) compared to the Systemic TXA (33%) and No TXA groups (57%) (p=0.0025) Conclusion: In conclusion, the present study is confirmative of the effectiveness of local TXA application in the reduction of postoperative bleeding in soft tissue surgery procedures.